Learning on Harmony in the Musical Work Aranti's Code - Mahameru, Erucakra; Panggabean, Ance Juliet; Batubara, Junita (Bulletin of Science Education, 2024)
The musical work entitled "Aranti's Code" means dark power where humans have this power in a dark world. Humans are controlled by a system above the applicable regulations. The method used in the study is a qualitative descriptive method with a scientific approach in the form of music analysis. The work "Aranti's Code" is an instrumental work that uses improvisation in vocal form. The work "Aranti's Code" has tonal independence in modal harmony. This can be seen from the tone scale of the Universe Modal Scale. From the results of the study, it has the form of three complex parts or three large parts, namely Ak (A complex), Bk (B complex), Ck (C complex). The duration of the work "Aranti's Code" is 3 minutes 46 seconds. In the first part, it is played with polymodality, free time signature implemented in 15/8 and played with a moderate tempo, then there is a change with polytonality, free time signature implemented in 15/8 and the tempo becomes allegro, andante, and lento. Each part has a different structure, giving rise to tonal independence in the concept of combining jazz music (Muhammad Akbar, Evolution of Jazz Erucakra Mahameru- Neo Progressive Jazz: Republika Daily 2011). Meanwhile, the review of harmony in this musical work is viewed from four components, namely, chord progression, open harmony, closed harmony, cadence, and modulation where the visible harmonization is ambiguous harmony. From the results of this study, it can be seen that in this musical work, the ambiguous harmonic chord progression is dominated by polytonality and polymodality. This musical work uses three types of cadences, namely augment cadences, inserted cadences, and shortcut cadences, while the modulation in this work seems complicated. Keywords: Compositional Works, Composers, Music Analysis, Polytonality & Polymodality